2019
DOI: 10.1627/jpi.62.157
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Hydrocarbon Fuels from Plant Oils for Diesel and Gasoline

Abstract: The issues of global CO2 emissions and depletion of non-renewable energy resources associated with fossil fuels encourage the use of plant oils (both edible and non-edible) as biofuel sources. This review summarizes the literature on renewable hydrocarbon fuel production, including feedstock choice, oil extraction, and production processes. Plant oils can be upgraded into hydrocarbon biofuels by catalytic cracking or deoxygenation reactions, such as hydrodeoxygenation, decarboxylation and decarbonylation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 145 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Catalytic hydroconversion of higher carbon number aliphatic carboxylic acids (C $ 12) (entries 1-5) resulted higher selectivity towards alkanes than that of lower carbon number (C5-C9) (entries 6-9). Moreover, Ru-(0.026)MoO x /TiO 2 catalyst was also active for hydroconversion of typical biomass-derived dicarboxylic acids (e.g., levulinic acid and succinic acid) produced diols and lactone under mild reaction conditions (entries [10][11].…”
Section: Catalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic hydroconversion of higher carbon number aliphatic carboxylic acids (C $ 12) (entries 1-5) resulted higher selectivity towards alkanes than that of lower carbon number (C5-C9) (entries 6-9). Moreover, Ru-(0.026)MoO x /TiO 2 catalyst was also active for hydroconversion of typical biomass-derived dicarboxylic acids (e.g., levulinic acid and succinic acid) produced diols and lactone under mild reaction conditions (entries [10][11].…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…5,6 The catalytic hydroconversion of fatty acids can be classied into three reactions: hydrodeoxygenation (HDO), hydrodecarbonylation (HDCO), and hydrodecarboxylation (HDCO 2 ), and a number of comprehensive reviews have been reported in the last decade. [7][8][9][10][11][12] HDCO and HDCO 2 yield hydrocarbons with one carbon atom less than the fatty acid precursor, while HDO gives hydrocarbons with the same chain length as the starting compounds. 13 Among these hydroconversion approaches, HDO, producing hydrocarbons without C-C bond cleavage of fatty acids, is more atom-efficient than the other methods (HDCO and HDCO 2 ) with C-C bond cleavage of the fatty acids.…”
Section: Introductionmentioning
confidence: 99%